The improvement of adaptive bit and power loading algorithm with low complexity in MIMO-OFDM systems - Liu Jiancai; Yang Wanwan; Zheng Weili; Wang Yafu; Ye Zhihui; Xu Jiakai; Ning Xinbao (2009 3rd International Conference on Internet Multimedia Services Architecture and Application, 2009)
Multiple-Input Multiple-Output Orthogonal Frequency Division Multiplexing (MIMO-OFDM) is a promising technology for high data rate transmission in wideband wireless systems for achieving high downlink capacities in future cellular systems. In this paper subcarrier and power allocation to each user at base-station is allocated to maximize the user data rates, subject to constraints on total power and bit error rate (BER). The chow-campello algorithm has been introduced and analyzed, and a low complexity algorithm has been proposed. The simulation results show that the proposed algorithm can achieve similar performance with much lower computational complexity, which indicates that the proposed algorithm is effective when compared to the existing algorithms.